2019
DOI: 10.1111/bjh.16255
|View full text |Cite
|
Sign up to set email alerts
|

Pixantrone plus rituximab versus gemcitabine plus rituximab in patients with relapsed aggressive B‐cell non‐Hodgkin lymphoma not eligible for stem cell transplantation: a phase 3, randomized, multicentre trial (PIX306)

Abstract: PIX306 was a phase 3, randomised, single-blind, multicentre trial conducted in adult patients with diffuse large B-cell lymphoma (DLBCL) or follicular lymphoma (FL) grade 3 who relapsed after ≥1 rituximab-containing regimen and were not eligible for a stem cell transplant. Patients were randomised 1:1 to pixantrone 50 mg/m 2 or gemcitabine 1000 mg/m 2 on days 1, 8 and 15 of a 28-day cycle, combined with rituximab 375 mg/m 2 on day 1, for up to six cycles. Patients were followed for up to 96 weeks. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…10,11 However, the phase III study PIX306, comparing the efficacy and safety of pixantrone with rituximab (PIX-R) versus gemcitabine with rituximab (GEM-R) in patients with relapsed (not refractory) aggressive B-cell NHL, deemed ineligible for ASCT (NTC01321541), failed to demonstrate any improvement in outcomes with pixantrone and rituximab as opposed to gemcitabine with rituximab. [12][13][14] In line with this were also findings of some real-world studies [15][16][17] which have shown overall disappointing outcomes of treatment with pixantrone and have therefore questioned the actual role of pixantrone in the current treatment of R/R aggressive lymphomas.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…10,11 However, the phase III study PIX306, comparing the efficacy and safety of pixantrone with rituximab (PIX-R) versus gemcitabine with rituximab (GEM-R) in patients with relapsed (not refractory) aggressive B-cell NHL, deemed ineligible for ASCT (NTC01321541), failed to demonstrate any improvement in outcomes with pixantrone and rituximab as opposed to gemcitabine with rituximab. [12][13][14] In line with this were also findings of some real-world studies [15][16][17] which have shown overall disappointing outcomes of treatment with pixantrone and have therefore questioned the actual role of pixantrone in the current treatment of R/R aggressive lymphomas.…”
Section: Introductionmentioning
confidence: 72%
“…No patient subgroups could be identified for whom the PIX-R arm was statistically more beneficial in terms of survival. 14…”
Section: Treatment Of R/r Patients Pixantrone With Rituximabmentioning
confidence: 99%
“…Until recently, the treatment options for the patients who are ineligible for AHCT or those whose lymphoma relapsed after AHCT were limited mainly to chemoimmunotherapy regimens such as R-GemOx (rituximab, gemcitabine, oxaliplatin), BR (bendamustine, rituximab), or pixantrone, or the off-label use of ibrutinib or lenalidomide; all are used with palliative intent given their limited efficacy [8][9][10][11][12][13]. Pixantrone, which was approved by the European Medicines Agency in 2012, also has modest clinical activity in relapsed/refractory DLBCL [14,15]. Historical data of patients with refractory DLBCL treated with the best therapies before the availability of novel treatments showed dismal outcomes with an objective response rate (ORR) and a complete response (CR) rate of 26 and 7%, respectively, and median overall survival (OS) of only 6 months [16].…”
Section: Introductionmentioning
confidence: 99%
“…The current treatments for DLBCL are mainly dependent on the clinical stages. The limited stage contains stages 1 and 2, the treatment guideline for which suggests the combination of systemic chemoimmunotherapy, including rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP), and the involved-field radiation therapy[ 3 , 4 ]. However, to some degree, involved-field radiation therapy is not applicable to patients with advanced stages.…”
Section: Introductionmentioning
confidence: 99%